2018
DOI: 10.15171/jcvtr.2018.08
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc Score Predict No-Reflow Phenomenon in Primary Percutaneous Coronary Intervention in Primary Percutaneous Coronary Intervention

Abstract: Introduction: No-reflow is one of the major complications of primary PCI in patients with acute ST elevation myocardial infarction. This phenomenon is associated with adverse outcomes in these patients. In the current study, we evaluated the effectiveness of CHA2DS2-VASc score in predicting no-reflow phenomenon. CHA2DS2-VASc score is a risk stratification method to estimate the risk of thromboembolism in patients with atrial fibrillation. Methods: In total, 396 patients with ST elevation myocardial infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
31
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 32 publications
11
31
4
Order By: Relevance
“…This study revealed a dual prognostic utility of CHA2DS2-VASc for both suboptimal reperfusion and short-term mortality. This coincides with many studies who found a useful surrogate measure of in-hospital mortality independent of nore low [5,12,[14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study revealed a dual prognostic utility of CHA2DS2-VASc for both suboptimal reperfusion and short-term mortality. This coincides with many studies who found a useful surrogate measure of in-hospital mortality independent of nore low [5,12,[14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…This study also revealed that lower systolic blood pressure was correlated with increased risk of no-re low independently. It might be related to reduction of coronary arterial perfusion pressure due to decreased blood pressure; this was similar to the results of Mirbolouk, et al [5]. Moreover, swelled myocardial cells concomitant with interstitial edema might lead to microvascular compression.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, it is important to predict and prevent the noreflow phenomenon with PPCI. Several recent studies have shown that some clinical biomarkers and parameters can predict the risk of no-reflow phenomenon, such as the WBC count [21], D-dimer [22], neutrophil/lymphocyte ratio [23] and CHA2DS2-VASc score [24]. In the present study, the patients of no-reflow group were found to be more older, diabetics, longer pain-to-balloon time, lower blood pressure, higher platelet counts and higher levels of D-Dimer and Cys-C.…”
Section: Discussionmentioning
confidence: 99%